Physio-mechanical properties of Minawar Granite: implications for building stone in Gilgit-Baltistan, Pakistan - Ahmad, Ishfaq; Gardezi, Syed Ahsan Hussain; Zhao, Meixia; Khan, Muhammad Jehangir; Qiuyan, Zhong; Ali, Massam; Zhang, Shuqi (Italian journal of engineering geology and environment, 2025)
Granite, as a building stone has been valued for centuries due to its strength, durability, and aesthetic properties. Granitic rock deposits are abundant in Pakistan, mostly in the northern regions that include the Himalayas and Trans-Himalayas. The present study aimed to investigate the physio-mechanical properties of Minawar granite, located near Gilgit city in Gilgit-Baltistan, Pakistan to assess its suitability as a construction material. Various standardized tests were performed on 14 rock samples, including uniaxial compressive strength (UCS), Schmidt hammer rebound values, point load index (PLI), ultrasonic pulse velocity (UPV), Brazilian tensile strength (BTS), porosity, and water absorption. Results reveal that fresh granite samples had an average UCS of 138.9 MPa, whereas dry and saturated samples had lower UCS values. Schmidt Hammer testing conducted on-site with natural environmental conditions impacted rebound values to be higher than those obtained in laboratory experiments. PLI values (5.32 to 9.13 MPa) revealed granite’s variability, although UPV measurements proved its high quality, with uniform density and few internal faults. The BTS tests showed an average tensile strength of 17.76 MPa. Moreover, the water absorption of the granite samples was very low - average of 0.21% for a fore mentioned commercial granites which is the reason to have an extremely good physical endurance considering material durability and resistance to weathering; low porosity and low water absorption make it ideal for moisture-rich conditions. Our results reveal that the Minawar granite meets and exceeds standard dimension stone specifications, confirming its superior quality and durability as a construction material for both indoor and outdoor use. These findings provide useful insights for future construction projects, demonstrating Minawar granite’s ability to deliver higher performance and longevity.